Diabetes Mellitus-Related Neurobehavioral Deficits in Mice Are Associated With Oligodendrocyte Precursor Cell Dysfunction - Wang, Li-Ping; Geng, Jieli; Liu, Chang; Wang, Yuyang; Zhang, Zhijun; Yang, Guo-Yuan (Frontiers in Aging Neuroscience, 2022)
Recent clinical studies demonstrated an increase of the incidence of neurobehavioral disorders in patients with diabetes mellitus. Studies also found an association between severity of diabetes mellitus and the progression of white matter hyperintensity on magnetic resonance imaging, which conferred risk for developing cognitive impairment. Since oligodendrocyte precursor cells participated in white matter repair and remodeling after ischemic brain injury, we explored whether hyperglycemia induced neurobehavioral deficits were associated with dysfunction of oligodendrocyte precursor cells. Adult male C57BL/6 mice (n=40) were randomly divided into 4-week diabetes, 8-week diabetes and control groups. Experimental diabetic mice were induced by streptozotocin injection. Learning and cognitive function, exploratory, anxiety and depression behaviors were assessed by Morris water maze, open field test, elevated plus maze, and tail suspension test, respectively. Immunofluorescence staining of neuron-glial antigen 2 and myelin basic protein were performed. Oligodendrocyte precursor cells were cultured in different glucose level to explore possible mechanism in vitro. The learning and cognitive function of 4-week and 8-week diabetic mice were attenuated compared to the control group (p<0.05). The diabetic mice had less exploratory behavior compared to the control (p<0.05). However, the diabetic mice were more likely to show anxiety (p<0.05) and depression (p<0.01) compared to the control. Further study demonstrated the number of oligodendrocyte precursor cells and the level of myelin basic protein expression were decreased in diabetic mice and the migration and survival ability were suppressed in the hyperglycemic environment in vitro (p<0.05). Our results demonstrated that diabetes mellitus induced neurological deficits were associated with the decreased number and dysfunction of oligodendrocyte precursor cells.